2018
DOI: 10.1371/journal.pntd.0006179
|View full text |Cite
|
Sign up to set email alerts
|

L-arginine supplementation reduces mortality and improves disease outcome in mice infected with Trypanosoma cruzi

Abstract: Chagas disease caused by Trypanosoma cruzi is a neglected disease that affects about 7 million people in Latin America, recently emerging on other continents due to migration. As infection in mice is characterized by depletion of plasma L-arginine, the effect on infection outcome was tested in mice with or without L-arginine supplementation and treatment with 1400W, a specific inhibitor of inducible nitric oxide synthase (iNOS). We found that levels of L-arginine and citrulline were reduced in the heart and pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
26
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 41 publications
1
26
0
Order By: Relevance
“…Moreover, after a global metabolomic analysis we found elevated levels of asymmetric+symmetric dimethyl-arginine (ADMA+SDMA) after infection in heart and plasma (Gironès et al, 2014 ) and confirmed elevated levels of ADMA in plasma (Carbajosa et al, 2018 ). ADMA is a product nuclear proteolysis by arginine methyltransferases (Teerlink, 2005 ), and is an endogenous inhibitor of iNOS that in combination with L-arginine regulates NOS activity (Blackwell, 2010 ).…”
Section: Myeloid Subsetsmentioning
confidence: 56%
See 1 more Smart Citation
“…Moreover, after a global metabolomic analysis we found elevated levels of asymmetric+symmetric dimethyl-arginine (ADMA+SDMA) after infection in heart and plasma (Gironès et al, 2014 ) and confirmed elevated levels of ADMA in plasma (Carbajosa et al, 2018 ). ADMA is a product nuclear proteolysis by arginine methyltransferases (Teerlink, 2005 ), and is an endogenous inhibitor of iNOS that in combination with L-arginine regulates NOS activity (Blackwell, 2010 ).…”
Section: Myeloid Subsetsmentioning
confidence: 56%
“…It is worth mentioning that a decrease in L-arginine causes down regulation iNOS expression (Konig et al, 2009 ) and reduces NO production by substrate competition. Notably, L-arginine administration to infected mice incremented plasma L-arginine and NO levels, significantly decreased parasitemia, heart parasite burden and clinical score, while increasing mice survival and cardiac performance (Carbajosa et al, 2018 ). In this direction, L-arginine treatment has been also shown to be beneficial in preventing Trypanosoma cruzi vertical transmission in rats (da Costa et al, 2014 ) and in patients affected by Dilated Cardiomyopathy, which clinically is the most similar to Chagas cardiomyopathy (Kralova et al, 2015 ).…”
Section: Myeloid Subsetsmentioning
confidence: 99%
“…The cardiac expansion of MDSCs is related to tissular damage and parasite persistence, because these cells were the most important source of NO leading to the immune response suppression . Based on this data, it has been proposed a new therapeutic approach against this disease, consisting in the administration of L‐arginine . Interestingly, the treatment with L‐arginine in mice improves survival rates and parasite clearance, preventing an excessive cardiac damage …”
Section: The Key Role Of Mdscs During Bacterial Viral and Parasiticmentioning
confidence: 99%
“…103,104 Based on this data, it has been proposed a new therapeutic approach against this disease, consisting in the administration of L-arginine. 105 Interestingly, the treatment with L-arginine in mice improves survival rates and parasite clearance, preventing an excessive cardiac damage. 105 Toxoplasma gondii is an obligate intracellular parasite that belongs to the Apicomplexa phylum.…”
Section: Parasitic Infectionsmentioning
confidence: 99%
See 1 more Smart Citation